BP4 DALAM KONTESTASI MASYARAKAT TRADISIONAL DAN URBAN (Studi Terhadap Persepsi Masyarakat Kota Metro Lampung) - Setiawan, Wahyu (P3M STAIN Jurai Siwo Metro, 2013)
BP4 as mariage concelling formed Government got challenges in the globalization. Modernity led to changes in the value and shifting patterns of family relationships in Indonesia. This paper aimed to see the existence of BP4 in that social changes. This research is a field-research in the form of case studies. Data collected through interview, observation, and documentation, with the qualitative-inductive analysis. This paper shows that the process of modernizing influences patterns of kinship. On the basis of traditional society, the influence of family structure to form an modified extended family. While communities with urban characteristics form patterns of quasi-conjugal family. The differences of family structure affect the viewpoints relating to marital problems, divorce, and the role of the BP4. Society looks at the role of the guidance and efforts of the BP4 extension pre-wedding is simply as an administrative issue. So, advices pre-marriage and role of marriage conceling are ineffective. Social changes lead to institution was estranged from society. Society does not know the existence of the BP4 in keeping and maintaining the integrity of the household.Â Keywords: BP4, traditional, urban, perception